User Interface Implementation Using User Centered Design (UCD) with Usability Testing Evaluation - Santi Purwanti; Jaja jaja; Rakhmayudhi Rakhmayudhi (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2025)
User Interface (UI) design plays a crucial role in enhancing user interaction, efficiency, and satisfaction in digital information systems. This study aims to design and evaluate the login module of the membership information system for Kelompok Seni Sigertengah using the User Centered Design (UCD) approach. The research methodology follows the UCD framework based on ISO 9241-210, which includes understanding the usage context, identifying user requirements, designing prototypes, and conducting evaluations through usability testing. Data were collected through observation, interviews, documentation studies, and prototype testing involving five representative users. The results show that the questionnaire scores ranged from 4.0 to 4.8, with an overall score of 4.43 out of 5, categorized as “Very Good.” Qualitative findings further indicate that the UI is easy to use, reflects local artistic identity, and improves both user comfort and system access efficiency. Therefore, the application of UCD has proven effective in producing a user interface design that meets user needs and is feasible to be implemented as a development model for UCD-based UI in arts and culture MSMEs.